Sustaining the Job Perfomance of Public Workers by Upholding the Work-Life Balance, and Self-Efficacy - Asniwati, Asniwati (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study explores how work-life balance and self-efficacy affect employee performance at the Cooperative and SMEs Office of South Sulawesi, Indonesia, with job satisfaction as a mediating variable. The research offers a clearer view of how these factors influence performance through different channels. Using a saturated sample of 188 civil servants and path analysis, the study finds that self-efficacy improves both job satisfaction and performance. Work-life balance improves performance but does not affect job satisfaction. Job satisfaction helps explain the effect of self-efficacy on performance, but not the effect of work-life balance. These results show that confidence and personal agency play a stronger role than work-life arrangements in driving public employee performance. For managers, this means focusing on self-efficacy development may offer more impact than relying on structural policy changes alone.